ETIOPATHOGENESIS OF DYSPLASTIC PROCESSES OF THE CERVIX (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
Cervical dysplasia (intraepithelial neoplasia) is a pathological change in the epithelium covering it. Atypical cells appear among healthy cells. They have an abnormal structure, size, shape, and development program. Such cells disrupt the structure of the epithelial layers. The peak incidence occurs at the age of 25-35 years. Dysplasia is considered a precancerous tissue change, but at an early stage the process is reversible. The disease is insidious - obvious clinical symptoms are absent for a long time. Simple screening, which is part of a preventive examination, helps to detect it at a safe stage.